2014
DOI: 10.1016/j.placenta.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2D3 suppresses COX-2 up-regulation and thromboxane production in placental trophoblast cells in response to hypoxic stimulation

Abstract: In this study, we determined if vitamin D could inhibit oxidative stress-induced thromboxane production by placental trophoblasts. Trophoblast isolated from normal placentas were stimulated with CoCl2, a hypoxic mimicking agent, with or without pretreatment of 1,25(OH)2D3. Soluble phospholipase-A2, metabolites of thromboxane-A2 and prostacyclin, and 8-isoprostane were measured. Expression of cyclooxygenase-1 (COX-1), COX-2, and heme oxygenase-1 (HO-1) were determined. We found that pretreatment of trophoblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…In keeping with this action to enhance antioxidant pathways, vitamin D increased the ratio of intracellular reduced to oxidized glutathione and decreased the production of 8-isoprostane. This action of vitamin D is consistent with previous evidence that it can protect various other types of epithelial cell from oxidative stress in vitro , including H 2 O 2 -treated prostatic and breast epithelial cells [51] [52] and CoCl 2 -treated trophoblasts [53]. Similarly, using immortalised epithelial cell lines, notwithstanding that immortalised cell lines are known to manifest distinctly different responses to vitamin D [54], it has been shown that vitamin D can abrogate impairment caused by oxidative stress of nuclear translocation of the ligand bound glucocorticoid receptor [55].…”
Section: Discussionsupporting
confidence: 90%
“…In keeping with this action to enhance antioxidant pathways, vitamin D increased the ratio of intracellular reduced to oxidized glutathione and decreased the production of 8-isoprostane. This action of vitamin D is consistent with previous evidence that it can protect various other types of epithelial cell from oxidative stress in vitro , including H 2 O 2 -treated prostatic and breast epithelial cells [51] [52] and CoCl 2 -treated trophoblasts [53]. Similarly, using immortalised epithelial cell lines, notwithstanding that immortalised cell lines are known to manifest distinctly different responses to vitamin D [54], it has been shown that vitamin D can abrogate impairment caused by oxidative stress of nuclear translocation of the ligand bound glucocorticoid receptor [55].…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed that aspirin probably inhibits the production of sFlt1 by the COX-1 pathway. Our study also showed that, hypoxia did not change COX1 and COX2 mRNA expression although some have reported that the hypoxia mimic, CoCl 2 increases COX2 but not COX1 in trophoblasts and others have reported that hypoxia reoxygenation increases COX-1 and COX-2 expression in murine placental explants (44, 45). We found that both aspirin and sc-560 decreased COX1 mRNA expression while increasing COX2 mRNA expression.…”
Section: Discussionsupporting
confidence: 48%
“…Although it is not clear whether the VDR binds directly to the promoter of MMP2 and MMP9 genes, due to the available binding site of NFkB on the promotor of the MMP2 and MMP9 genes (Zhang et al, ; Andrés, ), it seems that reduction in MMPs expression may be done through NFkB deactivation. Anyway, reduced synthesis of proinflammatory cytokines such as IL‐6 and TNF‐α by monocytes (Zhang et al, ), reduced synthesis of adhesion molecule, c‐reactive protein (Brewer et al, ), COX‐1 (Sun et al, ), and phagocytic receptors such as CD36 (Oh et al, ) are observed under the influence of vitamin D. Despite these anti‐atherogenic effects, it is observed that 1,25‐dihydroxyvitamin D3 induces VSMC migration via activation of phosphatidylinositol 3‐kinase (Rebsamen et al, ).…”
Section: Vitamin Effects On Atherosclerosismentioning
confidence: 99%